2013
DOI: 10.1002/jcp.24352
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine, Adenosine Receptors and Their Role in Glucose Homeostasis and Lipid Metabolism

Abstract: Adenosine is an endogenous metabolite that is released from all tissues and cells including liver, pancreas, muscle and fat, particularly under stress, intense exercise, or during cell damage. The role of adenosine in glucose homeostasis has been attributed to its ability to regulate, through its membrane receptors, processes such as insulin secretion, glucose release and clearance, glycogenolysis, and glycogenesis. Additionally, adenosine and its multiple receptors have been connected to lipid metabolism by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 108 publications
0
48
0
1
Order By: Relevance
“…figure 1a,b), although the hypoxic decrease in CO 2 production in AMP-treated naked mole rats was significantly less than that observed in saline-treated animals (figure 1b). This difference may have been due to a secondary effect of AMP on the balance between the catabolism of lipids and carbohydrates as fuel substrates in hypoxic naked mole rats, although this requires further investigation [30,31]. These changes were also reversed following 30 min of recovery in normoxia (to 41…”
Section: Resultsmentioning
confidence: 97%
“…figure 1a,b), although the hypoxic decrease in CO 2 production in AMP-treated naked mole rats was significantly less than that observed in saline-treated animals (figure 1b). This difference may have been due to a secondary effect of AMP on the balance between the catabolism of lipids and carbohydrates as fuel substrates in hypoxic naked mole rats, although this requires further investigation [30,31]. These changes were also reversed following 30 min of recovery in normoxia (to 41…”
Section: Resultsmentioning
confidence: 97%
“…These receptors are found in muscle, liver, and adipose tissue, all of them heavily involved in blood glucose homeostasis. In adipose tissue (A1-subtype receptors), caffeine could result in increased lipolysis and a glucose-saving systemic effect (3,19,24,25,27,38); however, by antagonizing adenosine receptors on skeletal muscle (also A1-subtype receptors), caffeine increases glycolysis (27). In addition, adenosine receptors in Exercise and caffeine in diabetic ratsthe liver stimulate gluconeogenesis, glycogenolysis, and glucose release (14,15,18,21,27,36), all of which could be potentially antagonized by caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is an endogenous purine nucleoside that inhibits lipolysis by activation of the A1 adenosine receptor (A 1 AR), which decreases adenylyl cyclase activity and inactivates PKA. 43 While adenosine inhibits lipolysis at rest, studies that infused the adenosine receptor antagonist theophylline during exercise reported no change in lipolysis, 44 questioning the importance of adenosine regulation during exercise.…”
Section: Other Hormonesmentioning
confidence: 99%